The sun is late and so is the farmer - Stead, Philip Christian (Holiday House, 2022)
"On a peculiarly long night, three farm animals are resting comfortably in the barn when a realization slowly dawns on them... the sun is late to rise. So the trio sets out on a daring quest to bring the sunrise."--